2014
DOI: 10.1093/ehjci/jeu001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of left atrial volumes using three-dimensional wall motion tracking echocardiographic technology: comparison with cardiac magnetic resonance

Abstract: This study validates LA volume measurements obtained using the new and fast 3D-WMT technology, compared with CMR. This method is fast, accurate, and reproducible, and it allows a better classification of left LA enlargement severity compared with 2D-echo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Validation of 3DSTE atrial volumetry with cardiac magnetic resonance has been previously reported . Two‐dimensional and 3DSTE methods showed a satisfactory correlation in the assessment of RA volumes, in spite of 3D better reproducibility indicated by a lower inter‐observer difference and variability.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Validation of 3DSTE atrial volumetry with cardiac magnetic resonance has been previously reported . Two‐dimensional and 3DSTE methods showed a satisfactory correlation in the assessment of RA volumes, in spite of 3D better reproducibility indicated by a lower inter‐observer difference and variability.…”
Section: Discussionmentioning
confidence: 82%
“…A technical limitation is that the low temporal resolution of 3DSTE affects the ability to track anatomic details frame by frame and requires multibeat (six beats) acquisitions. Further research leading to improvements in both hardware and software is required to assess the feasibility of 3DSTE and the relative importance of current limitations, such as the low frame rates and suboptimal image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…different imaging hardware, imaging settings and analysis algorithms. [13][14][15] Cardiac magnetic resonance is considered gold standard in left atrial volumetry.…”
Section: Introductionmentioning
confidence: 99%
“…9 Currently, LA volume and function can be measured in several ways; [10][11][12] although the most common method is 2D echocardiography (2DE), 3D echocardiography (3DE) has recently emerged as a method of choice because of its availability, shorter time for measurement and reproducibility. [13][14][15][16] An even newer innovative measuring technique is 3D speckletracking (3DSTA), [17][18][19] but its prognostic ability is still unclear.…”
mentioning
confidence: 99%